A Conceptual Framework for Barriers to the Recruitment and Retention of Rural CVD Participants in Behavior Intervention Trials - Young, Lufei (GSTF J Nurs Health Care, 2015)
BACKGROUND: Rural residents diagnosed with cardiovascular disease (CVD) or with CVD-related risks are underrepresented in behavioral intervention trials based on an extensive review of published studies. The low participation rate of rural residents weakens both the internal and external validity of published studies. Moreover, compared to urban residents, limited research exists to describe the unique barriers that limit the participation of rural residents in behavioral intervention trials. OBJECTIVE: The purpose of this review is to identify a conceptual framework (CF) underpinning common barriers faced by rural CVD patients to enroll in behavioral intervention trials. METHODS: We conducted a literature review using several electronic databases to obtain a representative sample of research articles, synthesized the evidence, and developed a CF to explain the barriers that may affect the research participation rate of rural residents with CVD or related risks. RESULTS: We found our evidence-based CF well explained the barriers for rural CVD patients to take part in behavioral intervention trials. Besides contextual factors (i.e. patient, community and research levels), other common factors impacting rural patients’ intent to enroll are lack of awareness and understanding about behavioral trials, limited support from their healthcare providers and social circles, unfavorable attitudes, and the lack of opportunity to participating research. CONCLUSION AND IMPLICATION OF RESULT: The findings demonstrate the evidence-based model consisting of interlinked multi-level factors may help our understanding of the barriers encountered by rural CVD patients participating interventions to promote behavioral change. The implication for researchers is that identifying and developing strategies to overcome the barriers precedes conducting studies in rural communities.